Cover Picture: Reduction of Charge and Discharge Polarization by Cobalt Nanoparticles‐Embedded Carbon Nanofibers for Li–O2 Batteries (ChemSusChem 15/2015). Issue 15 (24th July 2015) - Kim, Yun‐Jung; Lee, Hongkyung; Lee, Dong Jin; Park, Jung‐Ki; Kim, Hee‐Tak
<x xml:space="preserve">Abstract</x> The Cover picture shows a possible solution to the low round‐trip efficiencies of Li–O2 batteries (the most promising next‐generation battery) owed to the poor reversibility of the formation of the discharge product Li2O2 and the associated high polarization potentials. This can be achieved by controlling the phase structure and morphology of Li2O2. By embedding Co nanoparticles in carbon nanofibers, a uniform film‐like amorphous Li2O2 is formed and both the charge and discharge overpotentials are decreased. More details can be found in the Full Paper by H.‐T. Kim et al. on page 2496 in Issue 15, 2015. (DOI: 10.1002/cssc.201500520).